Effects of stress-loading test methods on the degradation of light-emitting diode modules. (September 2016) - Cai, Miao; Yang, Daoguo; Zheng, Jianna; Huang, Jianlin; Liu, Dongjing; Xiao, Jing; Zhang, Ping; Zhang, Guoqi; Chen, Xianping
Abstract: This study investigates the degradation of light-emitting diode (LED) lamp modules by various stress–load test approaches, namely, step-up stress accelerated degradation testing, step-down stress accelerated degradation testing (SDSADT), and constant stress accelerated degradation testing. Two types of commercial LED lamps with different capabilities of heat dissipation (CHDs) are utilized in the experiment. LM-80 testing on two types of LED packages is further implemented to reproduce the degradation reaction of Lamp B. Result shows that SDSADT can effectively alleviate the initial increase in optical parameters. Lamp B with a strong CHD exhibits a similar lumen decay rate at each stress of step stress testing; this similarity implies that the decay rate of Lamp B is only related to the current loaded stress. The lumen decay rate of the initial decay paths for Lamp B as the thermal stress increases exhibits a parabolic law. This parabolic pattern is also detected in the LM-80 testing for the LED packages and is explained by the strong CHD of Lamp B. The thermally induced mechanisms, which influence the optical emission of LEDs, should be responsible for the parabolic decay law. Moreover, the color shift of the LED modules with increasing loaded stresses is more sensitive than lumen degradation. Highlights: The effects of stress-loading test methods on the decay of LED modules are studied. The lumen decay rate of LED Lamp B is only related to the current loaded stress. The color shift with increasing loaded stresses is more sensitive than lumen decay. Initial lumen decay rate for LED Lamp B and/or Package I exhibits a parabolic law. The thermally induced mechanisms should be responsible for the parabolic decay law.